PEMBELAJARAN SASTRA DI PERGURUAN TINGGI YANG BERKARAKTER (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2017)
Abstract: One of subject in the Department of Language and Literature Education Indonesia and is Indonesian literature or literature. This course not only teaches literary competence through theories, history, and literary criticism but demands learners or students to have attitudes and characters in accordance with the values ​​contained in literary works. Therefore, literary education relates to character education. Therefore literary learning should contain the character values ​​that correspond to that purpose. Such an attempt is to choose materials and literary works that contain character values. The material contains the values ​​of the characters such as literary psychology, one of the approaches in Literature Theory. Literary works taken can be novel such as Amba, novel of Laksmi Pamuntjak. The novel contains lots of character values, one of which is the responsibility. Thus, the student not only understands the literary knowledge but also achieves the establishment of the character and the noble character of integrity, integrity, and balance, in accordance with the standard of graduation competence. Abstrak: Salah satu mata kuliah yang diajarkan di Jurusan Pendidikan Bahasa dan Sastra Indonesia adalah Sastra Indonesia. Mata kuliah ini tidak hanya mengajarkan kompetensi kesusastraan melalui teori, sejarah, dan kritik sastra tetapi menuntut pembelajar atau mahasiswa untuk memiliki sikap dan karakter yang sesuai dengan nilai-nilai yang terdapat pada karya sastra. Oleh karena itu, pendidikan sastra berkaitan dengan pendidikan karakter. Untuk itu pembelajaran sastra harus memuat nilai-nilai karakter yang sesuai dengan tujuan itu. Salah upaya tersebut adalah memilih materi dan karya sastra yang memuat nilai-nilai karakter. Materi memuat nilai-nilai karakter tersebut di antaranya adalah psikologi sastra, salah satu pendekatan dalam Teori Sastra. Karya sastra yang diambil dapat berupa novel seperti novel Amba karya Laksmi Pamuntjak. Novel tersebut banyak memuat nilai-nilai karakter yang salah satunya adalah tanggung jawab. Dengan demikian, mahasiswa tidak hanya memahami pengetahuan sastra tetapi juga dapat mencapai pembentukan karakter dan akhlak mulia secara utuh, terpadu, dan seimbang, sesuai dengan standar kompentensi lulusan. Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v4i2.7452